2020
DOI: 10.1155/2020/8709375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of IOL Power Calculation Formulas for Pediatric Eyes in Children of Different Ages

Abstract: Purpose. This study aims to compare the accuracy of five intraocular lens (IOL) power calculation formulas (SRK/T, Hoffer Q, Holladay 1, Haigis, and Holladay 2) for pediatric eyes in children of different ages. Methods. In this prospective study, patients who received cataract surgery and IOL implantation in the capsular bag were enrolled. We compared the calculation accuracy of 5 formulas at 1 month postoperatively and performed subgroup analysis with the patients divided into three groups according to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Kou et al reported that SRK/T formula had smaller APE in each group (1.13 ± 1.27 D, 1.018 ± 0.70 D, and 0.80 ± 0.70 D respectively). 23 The smallest APE was found in group ≥5 years, while the present study found that APE in group ≥7 years was higher (1.42 ± 1.19 D). Kou et al did not analyze the difference among these groups, but Chang et al reported that prediction errors were not significantly associated with different ages in most formulas, including SRK/T.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Kou et al reported that SRK/T formula had smaller APE in each group (1.13 ± 1.27 D, 1.018 ± 0.70 D, and 0.80 ± 0.70 D respectively). 23 The smallest APE was found in group ≥5 years, while the present study found that APE in group ≥7 years was higher (1.42 ± 1.19 D). Kou et al did not analyze the difference among these groups, but Chang et al reported that prediction errors were not significantly associated with different ages in most formulas, including SRK/T.…”
Section: Discussioncontrasting
confidence: 59%
“…Kou et al did not analyze the difference among these groups, but Chang et al reported that prediction errors were not significantly associated with different ages in most formulas, including SRK/T. 23 , 24 Lee et al stated that age at IOL implantation has significant correlation with PE calculated by SRK/II, SRK/T, and Hoffer-Q formula. 25 The discordance between the present study results and several previous studies can be attributed to age distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple linear regression analyses from previous studies have demonstrated that age is significantly associated with postoperative refractive error (21,32,35,39). The current metaanalysis included pediatric patients aged 1.1-216 months, which covers the whole period of the eye development pf a child.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the descriptive characteristics of the included studies. A total of 1,647 eyes from 12 studies were enrolled in our meta-analysis (20,21,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Five of the studies were conducted in the United States, three in China, three in other Asian countries, and one in Canada.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We found in patients younger than 2 years old or with an AL≤21 mm, SRK/T formulas were relatively accurate, while Barrett and Haigis formulas were better in patients older than 2 or with an AL>21 mm. Later, we made further research to compare the accuracy of five IOL power calculation formulas (SRK/T, Holladay 1, Holladay 2, Hoffer Q and Haigis) for pediatric eyes in children of different ages, finding that SRK/T and Holladay 1 formulas were relatively accurate in patients younger than 2 years old, while the Haigis formula performed better in patients older than 2 [42] . In the study of O'Gallagher et al [43] , SRK/T was also the most accurate formula in predicting postoperative refraction for patients younger than 8 years old.…”
Section: Challenges Of Iol Implantation Decision Of Choosing Iol Powe...mentioning
confidence: 99%